1991
DOI: 10.1017/s0022215100117311
|View full text |Cite
|
Sign up to set email alerts
|

Terminal parotid duct carcinoma

Abstract: Terminal duct carcinoma of salivary glands is an uncommon, histologically distinctive, low grade malignant neoplasm arising from the intercalated salivary duct. We present a case arising eight years after removal of a parotid tumour reported as a pleomorphic adenoma. We describe the clinico-pathological features of the present tumour, illustrate the difficulties that may be encountered in differentiating it from other salivary gland tumours, and discuss the possible significance of the previous tumour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…PLGA occurs almost exclusively in minor salivary glands, and its origin in a major salivary gland is considered rare. 4,5 Although several reports have described PLGA of the major salivary glands, [6][7][8][9][10][11][12][13][14][15][16] most are single case reports and few reports have presented convincing histological evidence. 6,9,10,12,14 Therefore, the exact frequency, biological behaviour, and immuno histochemical characteristics of PLGA arising primarily in major salivary glands have not been well defined.…”
mentioning
confidence: 99%
“…PLGA occurs almost exclusively in minor salivary glands, and its origin in a major salivary gland is considered rare. 4,5 Although several reports have described PLGA of the major salivary glands, [6][7][8][9][10][11][12][13][14][15][16] most are single case reports and few reports have presented convincing histological evidence. 6,9,10,12,14 Therefore, the exact frequency, biological behaviour, and immuno histochemical characteristics of PLGA arising primarily in major salivary glands have not been well defined.…”
mentioning
confidence: 99%
“…Leventon et al 13 reported on a patient with a malignant oncocytoma diagnosed 9 years after excision of a pleomorphic adenoma of the ipsilateral parotid gland. A 68-yearold patient described by George et al 14 presented with a terminal duct carcinoma 8 years after excision of a pleomorphic adenoma of the ipsilateral parotid gland. In the experience of Gnepp et al, 15 the most commonly seen combination is a Warthin's tumor and carcinoma, while pleomorphic adenomas are infrequently associated with cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is useful to look more closely at some of the specific features of PLGA arising in the parotid gland. There have been 36 reported cases of PLGA arising in the parotid gland (Table 1) (George et al 1991;Mark et al 1991Mark et al , 1992Miliauskas 1991;Ritland et al 1993;Kemp et al 1995;Merchant et al 1996;Puxeddu et al 1998;Gibbons et al 1999;Nagao et al 2004;Tamiolakis et al 2004). The genesis was acceptable as de novo PLGA in eight cases and as ex pleomorphic adenoma in four cases.…”
Section: Clinical Features Of the Plga Of The Parotid Glandmentioning
confidence: 99%